2021
DOI: 10.1021/acs.jpcc.1c00155
|View full text |Cite
|
Sign up to set email alerts
|

Underlying Mechanisms of Hot Carrier-Driven Reactivity on Bimetallic Nanostructures

Abstract: Bimetallic nanostructures exhibit unique catalytic activity and selectivity that are not evident for their monometallic analogues. Such nanostructures contain plasmonic metals, such as gold or silver, which afford highly efficient harvesting of electromagnetic radiation and its conversion into hot carriers. These highly energetic species are transferred to the catalytic metal subcomponent of the bimetallic nanostructure, where a large spectrum of chemical reactions may be catalyzed. The strength of the electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(59 citation statements)
references
References 52 publications
11
47
0
Order By: Relevance
“…Specifically, at 30 μW (λ = 633 nm), AuNPs possess ∼12 MW·cm –1 whereas Au@PdNPs and Au@PtNPs show ∼50 MW·cm –1 and ∼70 MW·cm –1 , respectively. Our own results, as well as experimental findings reported by other groups, show that the intensity of the rectified electric field depends on the intensity of the incident laser light. , …”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Specifically, at 30 μW (λ = 633 nm), AuNPs possess ∼12 MW·cm –1 whereas Au@PdNPs and Au@PtNPs show ∼50 MW·cm –1 and ∼70 MW·cm –1 , respectively. Our own results, as well as experimental findings reported by other groups, show that the intensity of the rectified electric field depends on the intensity of the incident laser light. , …”
Section: Resultssupporting
confidence: 85%
“…Our group showed that AuNPs, Au@PdNPs, and Au@PtNPs exhibit drastically different intensities of the rectified electric field on their surfaces . Optical rectification is a second-order nonlinear effect that originates from damping of LSPRs on the nanostructures. , Such damping transforms the alternating current (AC) into a constant direct current (DC) field that can be quantified using molecular reporters. Using TERS and 4-nitrobenzenethiol as a molecular reporter, we found that Au@PtNPs and Au@PdNPs exhibited 4–6 times larger magnitudes of the rectified DC field compared to the intensity of electric field observed on the surface of AuNPs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations